Enzyme amplified immunoassay: a novel technique applied to direct detection of Chlamydia trachomatis in clinical specimens. Issue 10 (October 1985) - Pugh, S F; Slack, R C; Caul, E O; Paul, I D; Appleton, P N; Gatley, S
Abstract : Endocervical swabs from 212 women and urethral swabs from 100 men were tested by the routine methods for McCoy cell culture and simultaneously by a novel enzyme amplified immunoassay test to detect chlamydia antigen. Overall correlation of the amplified test with culture was 96.5%. The test proved to be a suitable screening procedure for genital chlamydial infection, particularly for large numbers of specimens or in cases in which culture was not available.